Cercaria-schistosomulum surface transformation of Trichobilharzia szidati and its putative immunological impact - Horák, P; Kovár, L; Kolárová, L; Nebesárová, J (Parasitology, 1998)
Schistosome cercariae of the genus Trichobilharzia are the causative agent of swimmers' itch. In order to characterize the changes in parasites during and after the penetration of the host skin, in vitro and in vivo (in ducks and mice) transformations of T. szidati cercariae to schistosomula were performed. Ultrastructural observation revealed that cercariae possess a simple outer tegumental membrane with a thick glycocalyx. As with human schistosomes, the latter structure disappears during transformation and a new double membrane with putative protective function is formed. Our biochemical and immunological observations showed that the carbohydrate-rich glycocalyx of cercariae is readily bound by lectins and antibodies. The in vitro transformation to schistosomula can be detected by enhanced reactivity of 2 lectin probes (PNA and ConA) with the surface. The in vivo-transformed (skin and lung) schistosomula appear to have few surface ligands for the 12 lectin probes being tested. Similarly, the cercarial surface and its remnants on the in vitro-produced schistosomula is recognized by sera from immunized mice and humans with cercarial dermatitis; the tissue schistosomula fail to react with these antibodies. The loss of surface targets as a part of parasite immune evasion within the host is discussed.
Keywords: Fluorescent Antibody Technique, Indirect; fluorescenční protilátková technika nepřímá; Microscopy, Electron; Mice, Inbred BALB C; elektronová mikroskopie; Schistosoma; Mice; Fluorescent Antibody Technique, Direct; fluorescenční protilátková technika přímá; sacharidy; zvířata; Humans; Host-Parasite Interactions; myši inbrední BALB C; protilátky helmintové; Carbohydrates; kachny; Ducks; myši; interakce hostitele a parazita; Antibodies, Helminth; Epitopes; lidé; epitopy; Animals